Newly plant-derived carbon in the deeper vadose zone of a sandy agricultural soil does not stimulate denitrification - Xu, Wenyi; Lennart Ambus, Per (Geoderma, 2024)
•δ13C in bulk C showed no C4-plant-derived C 20 years past C3-C4 plant transition.•δ13C in DOC and respired C revealed C4-plant derived C allocation in deep vadose zone.•Cold-DOC and its chemical lability increased at soil depths below 130 cm.•Soil respiration or denitrification enzyme activity did not rise at depths < 130 cm.•Deeper soil plant-derived C may not drive denitrification to mitigate NO3– leaching. Analysis of stable carbon (C) isotopic signatures (δ13C) in various soil C pools provides useful information on soil C sources, transport, and availability. Understanding the extent of deeper soil (below 40 cm) sequestration and transport of plant derived C is of particular interest as this provides a source for microorganisms to drive biological denitrification (as indicated by denitrification enzyme activity, DEA) and hence mitigate the nitrate leaching to groundwater. Meanwhile, studies on deeper soil C sequestration are rare due to methodological constraints. This study was done in deeper vadose zone (0–160 cm) of a sandy agricultural soil in a humid and temperature zone after a C3-C4 vegetation change taking advantage of the marked isotopic differences between C3 and C4 plants. It took place in a site previously grown with C3 crops (beet, barley, grass), but where C4 crops (maize) were grown continuously for the last 20 years. The other site where C3 crops were continuously grown was used for comparison. Specifically, the δ13C signature in top and deeper soil layers was used to distinguish between old C3– and newly C4-plant derived C in four C pools, i.e., bulk soil C, hot- and cold-water extractable C, and respired CO2-C. The δ13C signature between C3 soils and C3-C4 shifted soils was similar for bulk soil C but significantly different for water extractable and respired C pools. Hence, we estimated that the contribution of newly derived C to bulk soil C was negligible, whereas the contributions to the other C pools amounted up to 28.4 % along the soil profile. This emphasizes the importance of simultaneously analysing δ13C signature in various soil C pools to accurately assess C vertical transport and distribution. The concentrations of cold-DOC and values of specific ultraviolet visible absorbance of the wavelengths 254 and 280 nm decreased from 50 to 130 cm soil depths, while they increased below these depths. However, this suggested rise in C chemical quality at the deepest soil depths did not cause an increase in soil respiration activity or DEA, which was attributed to the protective effects of iron and aluminium oxides on C decomposition. Upon the application of labile C and N substrates, the deepest soil layers displayed a significantly increased DEA, suggesting the presence of a relatively abundant population of active denitrifying organisms. Overall, this study documents the presence of plant-derived C in the deeper vadose zone. Meanwhile, this particular C pool might not be an important substrate to drive deep-soil denitrification due to constraints imposed by the protection by metal oxides.